Revisiting hospital patient safety culture in China: a nationwide network analysis - Haoning Shi; Zhiyu Chen; Xingyao Du; Jing Jiang; Ying Peng; Chunni Wang; Shuangjiang Zheng; Qi Huang; Mingzhao Xiao; Qinghua Zhao; Huanhuan Huang (Archives of Public Health)
Abstract Background Patient safety culture (PSC) is crucial for reducing medical errors and improving patient outcomes globally. This study aims to identify key improvement targets in China’s PSC to promote a safer healthcare environment. Methods Data were extracted from two national PSC surveys conducted in 2016 and 2020 and were analyzed using the 12-dimensional Hospital Survey on Patient Safety Culture (HSOPSC) 1.0 questionnaire. Central targets were identified through strength, closeness, and betweenness centrality. Network stability was assessed using the case dropping bootstrap method. Results A total of 24,529 responses were included, with an average positive response rate of 63.92%. Teamwork within units had the highest rate, and nonpunitive response to error the lowest. Feedback and communication about errors showed the greatest strength (1.302), closeness (0.008), and betweenness (22), occupying a core node position in both genders and correlating strongly with communication openness. After the COVID-19 pandemic, the core node position of management support for patient safety has become more prominent. Conclusions While teamwork is a notable strength, there is room to enhance the nonpunitive response to errors. Improving feedback and communication practices can further bolster openness and collaboration within teams, leading to an overall healthier work environment.